PENGARUH APLIKASI KONSORSIUM MIKROBA PENITRIFIKASI TERHADAP KONSENTRASI AMONIA (NH3) PADA AIR TAMBAK - Wage Komarawidjaja (Jurnal Teknologi Lingkungan, 2003)
An experiment on the utilization of nitrifying bacteria in shrimps pond ecosystemwas conducted in the village of Grinting, Brebes Regency. This experiment hastwo treatment ponds. Pond A was put nitrifying bacteria on as a treatment andpond B was without its treatment. The impact of the treatment was indicated by ammonia concentration measured, in which pond A was lower than pond B. In other words proved that nitrification process in pond A ecosystem was accelerated by the addition of nitrifying bacteria.